(untitled) (Estudios Sociales, 2023)
This article investigates the characteristics and elements that make up the collective action frame of a group of sexual diversity organizations in the city of Santa Fe. With this objective, the perspective of the framing process is recovered to analyze the Documents written by the sexual activism of Santa Fe for the Prides of the city corresponding to the years 2017, 2018 and 2019 (in these documents the activists present the claims defined as the most relevant of each year). On the one hand, it investigates how organizations politicize the problems that affect them by configuring definitions, identifying those responsible and proposing solutions. In parallel, various discursive strategies used to enhance the arguments that make up the framework of socio-sexual activism are observed. Through its framework, the Santa Fe Sexual Diversity Movement, aims to demonstrate that while numerous sexual rights laws have been passed, little has changed in everyday life for LGBT+ people. This framework works for a wide range of victims who report various problems.